Study guides

☆☆

Q: In the quadratic equation ax2 plus bx plus c 0 if b2 - 4ac?

Write your answer...

Submit

Still have questions?

Related questions

The quadratic equation in standard form is: ax2 + bx + c = 0. The solution is x = [-b ± √b2- 4ac)] ÷ 2a You can use either plus or minus - a quadratic equation may have two solutions.

Write the quadratic equation in the form ax2 + bx + c = 0 The roots are equal if and only if b2 - 4ac = 0. The expression, b2-4ac is called the [quadratic] discriminant.

The discriminant of the quadratic polynomial ax2 + bx + c is b2 - 4ac.

Full equation is (-b +/- sqrt(b2 - 4ac))/2a. Try it with x2 - 2x - 3, where a = 1, b = -2 and c = -3...

It's when ax2+bx+c=0 if b2-4ac= is negative

x = [−b ± √(b2 − 4ac)]/2aA, B, and C can all correspond to the original quadratic equation as follows: ax2 + bx + c = 0The quadratic formula can only be used if the quadratic equation is equal to zero.If [ Ax2 + Bx + C = 0 ], thenx = [ -B +/- sqrt( B2 - 4AC ) ]/ 2A

How you solve an equation that doesn't factor is to plug a quadratic equation's format; ax2+bx+c into the quadratic formula which is x=-b+square root to (b2-4ac)/2a.

A quadratic equation.

The answer to this is the Quadratic Formula, which is: (-b +/- (b2 - 4ac)1/2 )/2a -- as you might have guessed, +/- means there are two solutions for this equation.

ax2 +bx + c To find roots of any quadratic equation. X = - b (+/-) sqrt(b2 - 4ac)/2a

It is the general form of a quadratic equation.

With the help of the quadratic equation formula

People also asked